Systematic Literature Review: The Effectiveness of Using Social Media as a Marketing Channel for MSMEs in Balikpapan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
On the effectiveness of using social media as a marketing channel for MSMEs in Balikpapan. MSMEs play a major role in the national and regional economy, but developments in digital technology have caused marketing patterns to change drastically from traditional methods to online media. Social media such as Instagram, Facebook, TikTok, and X are now effective marketing tools because they are able to reach a wide audience at a low cost. However, this effectiveness is highly dependent on content quality, consistent interaction, and the right marketing strategy. Although social media offers many opportunities, MSMEs in Balikpapan still face various obstacles, such as limited human resources with an understanding of digital content, a lack of ability to read marketing metrics, and limited advertising budgets. In addition, research on the effectiveness of social media on MSMEs, especially in Balikpapan, is still minimal. Therefore, this study was conducted to analyze the extent to which MSMEs utilize social media, assess its effectiveness through indicators such as reach, interaction, and sales, and identify supporting and inhibiting factors. The results of this study are expected to provide strategic recommendations for MSMEs and theoretical contributions to the development of digital marketing models.